Dental data of the Athens 2004 Olympic and Paralympic Games - Vougiouklakis, G.; Tzoutzas, J.; Farmakis, E. T.; Farmakis, E. E.; Antoniadou, M.; Mitsea, A. (International Journal of Sports Medicine, 2008)
The Athens University, School of Dentistry, accepted the challenge to organize the Dental Health Services in the Athens 2004 Olympic and Paralympic Games in order to provide the best quality of oral health services to the athletes, coaches, escort members and Olympic Village personnel. Data from the whole activity protocol of the Athens 2004 Games Dental Health Services - the reception, admission and treatment protocols, the facilities and the infrastructure, the number of cases treated per specialty and the experience gained - were recorded. During the Olympic Games, there were more than 1400 dental cases in more than 650 patients, elite athletes, escort members, coaches and staff of the Olympic Village. Among them 313 fillings, 100 root canal therapies, 57 mouthguards and 9 dental trauma cases were treated. During the Paralympic Games, there were more than 240 dental cases in more than 220 patients. Among them 73 fillings, 12 root canal therapies, 21 extractions and 3 dental trauma cases were treated. In such events, highly trained dentists are needed and if possible, specialized in operative dentistry or endodontics. The role of team dentist seems to be of great importance.